Ethical leadership and public sector performance: mediating role of corporate social responsibility and organizational politics and moderator of social capital - Mohamed Abdi, Ahmed Nor; Hashi, Mohamed Bile; Latif, Khawaja Fawad (2024)
Evidence from the body of knowledge shows that ethical leadership influences organizational outcomes. Thus, drawing on social learning and social exchange theories, this study empirically examines the impact of ethical leadership on public sector organizational performance, focusing on the mediating effects of perceived organizational politics and corporate social responsibility and the moderating role of organizational social capital. A quantitative cross-sectional online survey was conducted using a convenience sampling strategy to collect data from 292 federal government employees and federal member state employees across Somalia. Structural equation modeling (SEM–PLS) was used to analyze the data using SmartPLS4. The results reveal that ethical leadership directly affects organizational performance, perceived organizational politics, and corporate social responsibility. Furthermore, perceived organizational politics partially mediate the relationship between ethical leadership and organizational performance. This study offers practical recommendations for public sector agencies and policymakers to enhance organizational performance through ethical leadership. This study fills a literature gap by exploring the association between ethical leadership and organizational performance in the public sector, specifically in Somalia. Various mediating and moderating factors have deepened our understanding of how ethical leadership influences organizational performance in the public sector.